An innovative structured fruit (SF) product made from litchi juice, king oyster mushroom (Pleurotus eryngii) and gellan gum: Nutritional, textural, sensorial properties. (December 2021) - Chang, Xinyue; Yang, Ao; Bao, Xin; He, Ze; Zhou, Kai; Dong, Quan; Luo, Wei
Abstract: The present study prepared an innovative structured fruit (SF) product based on king oyster mushroom ( Pleurotus eryngii ), litchi juice and gellan gel, and evaluated its textural, nutritional and sensorial properties. The lyophilized mushroom semi-ball sample was immersed in litchi juice containing different concentrations of gellan gel (0.25% and 0.5%), the SF products were obtained after the gelation of gellan gel. The nutritional analysis showed that the SF product possessed higher fiber and protein content, while lower sugar content than fresh litchi fruit. It retained about 30%–50% ascorbic acid, total phenols and total antioxidant capacity of fresh litchi due to the heating process during gel formation. Texture profile analysis revealed that gellan gum improved the texture properties of the structured fruit on hardness, cohesiveness, gumminess, chewiness, and resilience. Sensory descriptive analysis found that most sensorial attributes were highly remained in the final product, but the juiciness was significantly decreased by the addition of gellan gum. Scanning electron microscopy (SEM) observation revealed the synergistic effects between the mushroom and gellan gel resulted in the improved structure properties. In conclusion, the SF product could be a good solution for improving nutritional intake and reducing fruit wastage. Highlights: Innovative structured fruit from litchi juice, king oyster mushroom and gellan gum. Texture was much improved by the combination of king oyster mushroom and gellan gel. Synergistic effects improved structure properties rather than simple combination. The structured fruit has higher protein and fiber content while lower sugar content. Considerable ascorbic acid and phenols content, and antioxidant capacity remained.